Regulations on Valuation of Intellectual Property Rights as Credit Collateral to Ensure Legal Certainty for Financing Institutions - Izza, Noor Lailatul (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
The development of a knowledge-based and innovation-based economy places Intellectual Property Rights (IPR) as a strategic asset with economic value and financing potential. In the Indonesian legal system, the recognition of IPR as an object of credit collateral has been normatively accommodated through Law Number 42 of 1999 concerning Fiduciary Guarantees and various IPR sectoral laws. However, this recognition has not been followed by standardized and integrated valuation regulations, thus creating problems of legal certainty for financing institutions. This research is a normative legal research with a limited legislative, conceptual, and comparative approach. The results show that the lack of technical norms regarding valuation standards, regulatory fragmentation between the legal regimes of guarantees, banking, and IPR, and limited appraisal institutions cause IPR to not function optimally as credit collateral. This condition has an impact on increasing the risk of disputes, weakening the function of guarantees as a risk mitigation instrument, and limited access to financing for creative MSMEs. Therefore, regulatory strengthening is needed through codification of national standards for IPR valuation, harmonization of cross-sectoral regulations, certification of specialized appraisers, establishment of a national IPR value database, reformulation of execution mechanisms, and affirmative action policies for innovation-based financing. This strengthening is a prerequisite for ensuring legal certainty for financing institutions and encouraging the optimization of IPR as an instrument of national economic development.